Catalyst-free nitration of the aliphatic CH bonds of tertiary β-keto esters with tert-butyl nitrite: Access to α-quaternary α-amino acid precursors. (8th June 2022) - Han, Fu-Zhong; Li, Lin-Lin; Jia, Li-Na; Hu, Xiang-Ping
Graphical abstract: An efficient catalyst-free direct nitration of the aliphatic hydrocarbon bonds of tertiary β-keto ethers using tert- butyl nitrite as a nitrating reagent is described. This radical nitration protocol tolerants diverse functional groups, leading to the preparation of linear and cyclic α-nitro-β-keto ester derivatives in good to excellent yields under mild conditions. In addition, the nitration product 3a was applied to the concise synthesis of α-quaternary α-amino acid ether 4 in the presence of zinc power and acetic acid. Abstract: An efficient catalyst-free direct nitration of the CH bonds of tertiary β-keto esters using tert- butyl nitrite as a nitrating reagent is described. This radical nitration protocol tolerants diverse functional groups, leading to the preparation of linear and cyclic α-nitro-β-keto ester derivatives in good to excellent yields under mild conditions. In addition, the nitration product 3a was applied to the concise synthesis of α-quaternary α-amino acid 4 in the presence of zinc power and acetic acid.